2021
DOI: 10.3390/cells10061542
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Physical Activity via the Adaptation of Astrocytes

Abstract: The multifold benefits of regular physical exercise have been largely demonstrated in human and animal models. Several studies have reported the beneficial effects of physical activity, both in peripheral tissues and in the central nervous system (CNS). Regular exercise improves cognition, brain plasticity, neurogenesis and reduces the symptoms of neurodegenerative diseases, making timeless the principle of “mens sana in corpore sano” (i.e., a healthy mind in a healthy body). Physical exercise promotes morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 123 publications
0
21
0
Order By: Relevance
“…Physical exercise has beneficial effects on both peripheral tissues and CNS, and is a kind of safe and effective intervention to improve cognitive function ( Maugeri et al, 2021 ). In human and animal models, the multiple benefits of regular physical exercise have been fully demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical exercise has beneficial effects on both peripheral tissues and CNS, and is a kind of safe and effective intervention to improve cognitive function ( Maugeri et al, 2021 ). In human and animal models, the multiple benefits of regular physical exercise have been fully demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more studies have shown that the changes in astrocytes may be a key mechanism accounting for the improvement of cognitive and executive functions related to exercise ( Li et al, 2021 ; Maugeri et al, 2021 ). Astrocytes are the main homeostasis and defense elements of the brain, helping to maintain cognitive reserve through a variety of mechanisms ( Verkhratsky et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that physical exercise promotes morphological changes in astrocytes, and astrocytes may contribute to episodic memory function [ 42 , 140 ]. Astrocytic activation is necessary for synaptic plasticity and is sufficient to induce NMDA-dependent long-term potentiation in the hippocampus in a task-specific way, coupled with learning [ 138 ].…”
Section: Dentate Gyrus Astrocytes Long Life Sedentary Lifestyle and D...mentioning
confidence: 99%
“…As a function of environmental stimuli [ 41 , 42 ], age [ 43 , 44 ], or the presence of other pathology [ 45 , 46 , 47 ], astrocytes differentially respond to changes in the microenvironment of the brain, in both form and function [ 48 , 49 ]. For example, physical exercise induces astrocyte proliferation and morphological changes, which alters the interplay between astrocytes, microglia and neurons to enhance neuroplasticity [ 23 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%